(untitled) (Web of Teachers: Inderscience Research, 2023)
Today English is the language of communication around the world, no other language is used as globally and widely as English. It is the language of world business and politics. In many educational institutions, students study English as a compulsory subject in their academic programs, as it is a subject that contributes to the graduate’s further career in certain fields of activity and business. This article reveals the main problems and difficulties in mastering the necessary competencies when learning English, which most of the students face. The main task is to consider ways and methods to improve language acquisition and overcome emerging problems in learning English, which are simple and effective in implementation and application in practice in the learning process.